Impact of social media on students’ academic efficiency at Industrial University of Ho Chi Minh city - Duong, Thị Ánh Tiên; Nguyen, Thị Thúy Việt; Nguyen, Thị Thùy; Nguyen, Công Du (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
This article studies the impact of social media on student learning outcomes. Survey data includes 184 students from various majors at Industrial University of Ho Chi Minh City. Using a quantitative research methods, the research results show that except for the resource sharing factor, the remaining factors of social media have a positive impact on learning outcomes in descending order such as communication ability, perceived ease of use, erception of usefulness, commitment and collaborative learning. The research results highlight communication ability as a new point in the impact of communication on student learning outcomes. The research results are the basis for the authors to propose administrative implications to recommend appropriate social network usage behavior so as not to affect students’ academic results.